2019
DOI: 10.1111/codi.14536
|View full text |Cite
|
Sign up to set email alerts
|

Drain fluid amylase as a sensitive biomarker for the early detection of anastomotic leakage in ileal pouch surgery

Abstract: Aim We studied the levels of amylase in drain fluid to investigate its utility as a biomarker of anastomotic leak in ileal pouch patients who did not have a covering loop ileostomy. The luminal contents of the small intestine are high in amylase. Ileal J pouches are formed for restoration of continuity in patients with ulcerative colitis after removal of the colon and rectum. A drain is placed alongside the ileal pouch in the pelvis. Method This study is a retrospective analysis of prospectively collected dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…A local biomarker in the setting of IPAA is amylase, which can be measured simply and quantitatively in drain fluid. It has already been shown, in an early study from this institution, that amylase is present in high concentrations in enteric content from the rectal tube [ 25 ]. There is ongoing research to assess its utility in early diagnosis of AL.…”
Section: Discussionmentioning
confidence: 99%
“…A local biomarker in the setting of IPAA is amylase, which can be measured simply and quantitatively in drain fluid. It has already been shown, in an early study from this institution, that amylase is present in high concentrations in enteric content from the rectal tube [ 25 ]. There is ongoing research to assess its utility in early diagnosis of AL.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge could be applied to the sampling and analysis of abdominal wound or drain fluid to indicate a communication with the gut. In preliminary studies, the detection of amylase in pelvic drain fluid has been evaluated as a potential biomarker of anastomotic leak in ileal pouch surgery 10 . Sampling amylase in abdominal wound fluid may similarly be utilized to detect if there is evidence of a direct communication with the ileal lumen and may be an adjunct to the diagnosis of an enterocutaneous fistula.…”
Section: Discussionmentioning
confidence: 99%
“…In studies measuring extravasated intraluminal substances in drain fluid after low pelvic colorectal anastomoses, it has been shown that these substances are significantly elevated in the setting of anastomotic leak. 9 This protocol could offer a simple, quick, reliable and reproducible method for identifying the presence of Gastrografin in drain fluid in patients suffering an anastomotic leak and with high intraluminal concentrations of administered enteral Gastrografin. Indeed, regular DECT testing of ex vivo drain fluid may serve as a helpful biomarker and avoids any exposure of the patient to ionising radiation.…”
Section: Discussionmentioning
confidence: 99%